MapHead - Howarth, Lesley (London: Catnip, 2011)
MapHead is a visitor from the Subtle World it exists side by side with our own. He is based in a tomato house, the traveller has come to meet his mortal mother for the first time. But with all his dazzling alien powers can MapHead master the language of the human heart?
Keywords: Children's stories